The Effect of Additional Compensation on Employee Performance Mediated by Job Satisfaction of Employees of PT Telkom Indonesia Tbk. - Hazmanan Khair; Luthfiah Adira (Management Research and Behavior Journal, 2022)
The purpose of this research is to determine the effect of additional compensation on employee performance at PT Telkom Indonesia, Tbk Witel Medan. To determine the effect of job satisfaction and employee performance on additional compensation at PT. Telkom Indonesia, Tbk Witel Medan. To determine the effect of job satisfaction on employee performance at PT Telkom Indonesia, Tbk Witel Medan. To determine the effect of additional compensation and employee performance on job satisfaction at PT Telkom Indonesia, Tbk Witel Medan. The approach in this research is included in the quantitative research approach. The population used as a sample is all employees of PT Telkom Indonesia, Tbk Witel Medan, totalling 70 people. The data analysis technique in this study uses Structural Equational Modelling (SEM) using Smart-PLS 3. The results of testing the first hypothesis show that the additional compensation variable has a positive and significant effect on employee performance at PT Telkom. The results of testing the third hypothesis show that the additional compensation variable has a positive and significant effect on employee job satisfaction at PT Telkom. The results of testing the fifth hypothesis show that the job satisfaction variable has a positive and significant effect on employee performance at PT Telkom. The results of the sixth test show that employee job satisfaction mediates the effect of additional compensation on performance at PT Telkom by showing a positive but insignificant effect.